Effect of Medium on Fundamental Interactions in Gravity and Condensed Matter - Zhuk, Alexander; Shulga, Valerii (Frontiers in Physics, 2022)
Recently, it was shown that the gravitational field undergoes exponential cutoff at large cosmological scales due to the presence of background matter. In this article, we demonstrate that there is a close mathematical analogy between this effect and the behavior of the magnetic field induced by a solenoid placed in a superconductor.